A study of a late thirteenth-century composite Office book (Cape Town, National Library of South Africa,MS Grey 4b5) with reference to selected manuscript sources from the diocese of Münster in Westphalia - Werth, Keri Mariken (College of Music, 2019)
MS Grey 4b5 (Cape Town, National Library of South Africa, Grey Collection, ms. 4.b.5) is a composite Office book comprised of a noted breviary and an antiphoner. It is dated in the late 13th to early 14th century and is from the city of Münster, Westphalia. The notation of the melodies makes use of Hufnagelschrift and the texts show various stages of Textualis Gothica throughout the entirety of the book. This manuscript gives an indication of liturgical practices in the city of Münster prior to the Anabaptist takeover between 1533 and 1535. This investigation has confirmed a number of facts. Analysis of the text indicates that the breviary section is from the late 14th century as the scribe made use of the fully developed letter forms of Textualis Gothica script. The antiphoner section shows evidence of earlier stages of Textualis Gothica in its many hands, thus placing it in the late 13th century. The textual and notational hands overlap in such a way as to indicate that the antiphoner was written in the same location. Studies on the feast of Corpus Christi in Grey 4b5 with references to sources in Vincent Corrigan’s edition and other sources from Münster reveal that Grey 4b5 contains an early version of the standardised Office, as well as a wholly unique responsory and verse in Vespers. In the same vein, expansion of Morné Bezuidenhout’s initial investigation of the feast of Saint Liudger in Grey 4b5 confirms the manuscript’s provenance to be from the city of Münster. Musical editions of Corpus Christi and Saint Liudger are included in this investigation. Studies on late style characteristics of the music in the Office of Corpus Christi, with reference to research by David Hiley and Roman Hankeln, indicate that while Grey 4b5 contains an early version of the standardised Office of Corpus Christi, it shows slightly more radical features than other sources in this edition. Comparative studies of late style characteristics in the Office of Corpus Christi with Saint Liudger show that, despite its radical style, the musical items for Corpus Christi seemed to have been composed more conservatively than those for Saint Liudger. Additional analyses on contrafacta - with reference to László Dobszay and Janka Szendrei - and on the great responsories of Corpus Christi - with reference to Kate Helsen’s study - also support this evidence. Investigations on the musical content of Grey 4b5 reveal some items that are completely unique to the manuscript. There are also items in Grey 4b5 that correspond solely with sources in the diocese of Münster. A provisional index of the musical content of the Grey manuscript is provided at the end of this dissertation, the complete version of which will soon be available on the CANTUS database.